THE EFFECT OF SUMMARIZATION INSTRUCTIONAL STRATEGIES AND PRESENTATION FORMATS ON THE OUTCOMES OF HISTORICAL ARGUMENTATIVE REASONING (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The purpose of this research is to examine the effects of summarization instructional strategies and presentation formats on the learning outcomes of history argumentative reasoning. This study is designed as a factorial design. The subjects were the students enrolled in four state-owned sehior high school in Malang Regency. The main conclusions are presented as follow: (1) A significant difference existed for students who used the cause-effect graphic organizer summarization strategy to answer history argumentative reasoning post-test questions when compared to the written summarizing strategy, (2) There is no difference between those who were presented with present-subheadings presentation format and those who were presented absent-subheadings on answering history argumentative reasoning posttest questions, and (3) There is a significant interaction between the summarization instructional strategies and the presentation formats. The students who used cause-effect graphic organizer summarization strategy and were given with the present-subheadings presentation format significantly outperformed in the historical argumentative reasoning post-test scores than the other groups (graphic organizer and absent-subheadings group, written summarizing and with-subheadings group, and written summarizing and without-subheadings group).Key Words: summarization instructional strategy, presentation format, cause-effect graphic organizer, written summarizing, present-subheadings, historical argumentative reasoning.Tujuan dari penelitian ini adalah untuk mengetahui pengaruh strategi pembelajaran summarization dan format presentasi tentang hasil belajar sejarah penalaran argumentatif. Penelitian ini dirancang sebagai desain faktorial. Subjek penelitian adalah siswa terdaftar di empat sekolah SMA di Kabupaten Malang. Kesimpulan utama disajikan sebagai berikut: (1) Sebuah perbedaan yang signifikan ada bagi siswa yang menggunakan strategi peringkasan untuk menjawab sejarah argumentatif pertanyaan penalaran posttest bila dibandingkan dengan strategi meringkas tertulis, (2) Tidak ada perbedaan antara mereka yang disajikan dengan saat-subpos format presentasi dan mereka yang disajikan absen-subpos pada menjawab sejarah penalaran argumentatif pertanyaan posttest, dan (3) Ada interaksi yang signifikan antara strategi pembelajaran peringkasan dan format presentasi. Para siswa yang menggunakan sebab strategi pengelolaan peringkasan dan diberi dengan format presentasi signifikan mengungguli dalam skor penalaran posttest sejarah argumentatif daripada kelompok lain (pengelolaan grafis dan kelompok tanpa anak judul, meringkas tertulis dan kelompok dengan anak judul, dan meringkas tertulis dan kelompok tanpa anak judul). Kata Kunci: strategi pembelajaran peringkasan, presentasi, pengelolaan grafik sebab-akibat, ringkasan tertulis, presentasi, , format presentasi, sebab-akibat, tidak ada-subpos, penalaran argumentatif sejarah.